Instruction of Spanish Direct and Indirect Object Pronouns through Task-Supported Videoconferencing Instruction - Lopez Vera, Alexandra (Huarte de San Juan. Filología y Didáctica de la Lengua, 2023)
Task-supported videoconferencing instruction emphasizes learner centeredness and experiential learning in Second Language Acquisition (SLA). Still, relatively few studies have addressed the use of specific linguistic structures in online courses from a task-based perspective. The present study examines the effects of an online task-supported module on the acquisition of direct and indirect object pronouns in Spanish. These pronouns are used very frequently by proficient Spanish speakers, but are less used by Spanish learners because of their morphological and syntactic complexity. The results of this study demonstrate the benefits of using an online task-supported module specially designed to promote the use of direct and indirect object pronouns in Spanish through videoconference. Participants used the target structures on many occasions without being prompted to do so. The results suggest that the task-supported module is a promising approach to the teaching of grammar.